Transformasi Digital Dalam Proses Pembelajaran Studio Desain Komunikasi Visual Sebagai Refleksi Pasca Pandemi - Dita Saraswati; Nuning Y. Damayanti; Agung E.B. W.; Djuli Djatiprambudi (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
Visual communication design education in Indonesia has long applied studio-based teaching methods influenced by the history of the European design education system. In studio-based learning, students are required to master competencies formed from; personality competence, technical competence, communication competence, methodological competence, and social competence. In the studio room, student knowledge is developed by conducting training guided by lecturers. The studio trained technical exercises such as sharpening hand skills, processing taste, and shape. The studio also forms students' understanding of the design's concept. Gradually the quality in designing can be formed. With the Covid-19 pandemic, studio-based teaching methods have been forced to be carried out online. This article seeks to describe the forms and processes of change in learning in studios that use digital technology as a result of the pandemic conditions. By taking some examples of cases of application of learning in the design studio, the presentation intends to reflect a new learning style rooted in studio-based learning in visual communication design education and to present ideas that become material for further research for the development of learning methods in the field of design in the future.